2015
DOI: 10.1111/bjh.13338
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐intensified chemotherapy alone or in combination with mogamulizumab in newly diagnosed aggressive adult T‐cell leukaemia‐lymphoma: a randomized phase II study

Abstract: SummaryThis multicentre, randomized, phase II study was conducted to examine whether the addition of mogamulizumab, a humanized anti‐CC chemokine receptor 4 antibody, to mLSG15, a dose‐intensified chemotherapy, further increases efficacy without compromising safety of patients with newly diagnosed aggressive adult T‐cell leukaemia‐lymphoma (ATL). Patients were assigned 1:1 to receive mLSG15 plus mogamulizumab or mLSG15 alone. The primary endpoint was the complete response rate (%CR); secondary endpoints includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
184
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(188 citation statements)
references
References 29 publications
3
184
1
Order By: Relevance
“…One patient died because of CMV encephalitis. Furthermore, Ishida et al reported that 4 patients (14%) who received mLSG15 combined with mogamulizumab developed CMV infection, which was not observed in the patients who received mLSG15 therapy alone (12). This report suggested that the addition of mogamulizumab to systemic therapy might further increase the incidence of CMV infection.…”
Section: Discussionmentioning
confidence: 95%
“…One patient died because of CMV encephalitis. Furthermore, Ishida et al reported that 4 patients (14%) who received mLSG15 combined with mogamulizumab developed CMV infection, which was not observed in the patients who received mLSG15 therapy alone (12). This report suggested that the addition of mogamulizumab to systemic therapy might further increase the incidence of CMV infection.…”
Section: Discussionmentioning
confidence: 95%
“…Treatment is based on clinical signs, with skin-directed therapy or interferon associated with zidovudine in indolent cases and with systemic multidrug therapy or bone marrow transplantation in aggressive cases 1,18 . Phase 2 clinical trials with the anti-CCR4 monoclonal antibody mogamulizulab are currently being conducted, and these show promising responses thus far in refractory and aggressive cases ATLL 90 .…”
Section: Figure 5: Sézary Syndrome Erythroderma (Diffuse Erythema Anmentioning
confidence: 99%
“…17 Mogamulizumab, a humanized CCR4 antibody, is a newly developed antibody that is effective for refractory and relapsed ATL, and newly diagnosed ATL. [18][19][20][21] It provided a breakthrough paradigm shift to a molecule-targeted approach for ATL therapy. [18][19][20][21] Mogamulizumab attacks targeted ATL cells via antibody-dependent cellular cytotoxicity and natural killer cells.…”
Section: Introductionmentioning
confidence: 99%